Nematode assemblages in four ecosystems of Parque Nacional del Agua, Costa Rica - Varela-Benavides, Ingrid (2022)
The soil nematode fauna of five locations situated in Parque Nacional del Agua (PNA) in Costa Rica is characterized and analyzed. Four ecosystems were sampled in each location: primary (undisturbed) forest, secondary (naturally regenerated) forests, tree plantations (cleared and replanted with timber trees), and pastures (cleared of trees). Five soil samples of 100 g were analyzed in each location and ecosystem, resulting in a total of 100 samples. One hundred and thirty-one nematode genera were identified, and their abundance and biomass were estimated and analyzed by means of nonmetric multidimensional scaling (NMDS) and redundancy analysis (RDA). The observed nematode abundance was 1237 ± 520 specimens per soil sample for the whole survey, similar to previously reported from tropical soils. Dominance-diversity curves, based on nematode abundance, follow a similar ‘hollow curve’ pattern, with only 20 of the genera representing 84.6% of the total abundance, and only 12 of the genera representing 88% of the total biomass. Helicotylenchus, tylenchids, criconematids, Belondira, Longidorus, Xiphinema, Monotrichodorus, Prismatolaimus and Steinernema are important in the assemblages due their abundance or biomass in the different samples. Monotrichodorus and Discocriconemella appear related to undisturbed ecosystems, and they could have potential as disturbance indicators. Biomass-based dominance-diversity curves have similar qualitative and quantitative behavior to those observed in abundance distribution, but the dorylaims, Aporcelinus and Aporcelaimoides, which represented only the 0.35% of the abundance, having a major part of the total biomass (4.33%). NMDS analysis segregated locations into two groups, sampled sites were arranged according to the life zone where they belong. Ecosystems were segregated into natural ecosystems and plantations but having overlapping zones. Whereas RDA analysis indicated that organic matter and Cu are the most relevant edaphic variables for explaining the distribution of nematode assemblages, however few genera appear important in the ordination, Mesocriconema, Longidorus, Xiphinema and Belondira between them.